Preparation of photocrosslinked sol‐gel composites based on urethane‐acrylic matrix, silsesquioxane sequences, TiO2, and Ag/Au Nanoparticles for use in photocatalytic applications. Issue 10 (21st February 2015) - Chibac, Andreea L.; Melinte, Violeta; Buruiana, Tinca; Mangalagiu, Ionel; Buruiana, Emil C.
ABSTRACT An acid urethane oligodimethacrylate based on poly(ethylene glycol) was synthesized and used in the preparation of hybrid composites containing silsesquioxane sequences and titania domains formed through sol‐gel reactions along with silver/gold nanoparticles (Ag/Au NPs) in situ photogenerated during the UV‐curing process. The photopolymerization kinetics studied by Fourier transform infrared spectroscopy and photoDSC showed that the photoreactivity of the investigated formulations depends on the amount of titanium butoxide (5–20 wt %) added in the system subjected to UV irradiation. The introduction of 1 wt % AgNO3/AuBr3 in formulations slightly improved the degree of conversion but diminished the polymerization rates. The formation of hybrid materials comprising predominantly amorphous TiO2/SiO2 NPs, with or without Ag/Au NPs, was confirmed through specific analyses. The evaluation of photocatalytic activity demonstrated that the synthesized hybrid films are suitable for the complete removal of organic pollutants (phenolic compounds) from water under UV irradiation (200–350 min) at low intensity (found in the solar radiation). © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1189–1204